Relationship Between The Severity of Acne Vulgaris on The Face and Self Confidence in Adolescents - Diyanah, Urwatud; Widiyawati, Wiwik; Ernawati, Ernawati; Widiharti, Widiharti (INNOVATION RESEARCH JOURNAL, 2025)
Acne vulgaris is a chronic skin disease that occurs due to chronic pilosebaceous inflammation which is characterized by the presence of comedones, papules, pustules, nodules and cysts in the predilection areas which are usually the sebaceous glands such as the face, chest and upper back. This disease is not a dangerous disease but has a big impact on teenagers both physically and psychologically, causing anxiety and depression. A face with acne will also affect psychosocial development, including self-confidence. The aim of this research is to determine the relationship between the severity of facial acne and self-confidence in adolescents. The type of research used is quantitative with a cross-sectional approach. The population was 135 students and the sample used was 100 students using purposive sampling technique. Statistical tests use the Chi-square test. The research results showed that the severity of acne (acne vulgaris) on the face of 41 students (41%) was in the mild category. The incidence level of self-confidence among students is in the low category, as many as 66 people (66%). The significance value of the relationship between the severity of acne (acne vulgaris) on the face and self-confidence in adolescents shows that it has a significant r value of 0.001 < α (0.05). There is a significant relationship between the severity of facial acne (acne vulgaris) and self-confidence in adolescents.